Murine model of OPRM1 A118G alters oxycodone self-administration and locomotor activation, but not conditioned place preference. (1st May 2020) - Collins, Devon; Zhang, Yong; Blendy, Julie; Kreek, Mary Jeanne
Abstract: Mu-opioid receptors (MORs) mediate the rewarding properties of oxycodone and other prescription opioid medications, which have played a central role in the current opioid epidemic in the United States. The human mu-opioid receptor gene ( OPRM1 ) contains a functional single nucleotide polymorphism (SNP), A118G, which has been associated with altered opioid addiction risk, however the mechanisms responsible for this are not well understood. To explore this, we examined oxycodone conditioned place preference (CPP) and self-administration behavior (SA) in A112G mice, which possess a functionally analogous SNP in the mouse mu-opioid receptor gene ( Oprm1 ). For CPP, male and female A112G mice homozygous for the A112 (wild-type; AA) or G112 (GG) allele were conditioned with doses of 1 and 3 mg/kg across an 8-day period. For SA, mice were allowed to self administer oxycodone (unit dose 0.25 mg/kg/infusion, FR1) for 4h/day for 10 consecutive days. We observed no effects of genotype or sex on conditioned place preference behavior. Oxycodone 3 mg/kg increased locomotor activity in AA mice but not GG mice, and both male and female GG mice self-administered significantly more oxycodone compared to their wild-type AA littermates. These studies suggest that the G allele promotes greater opioid intake, which may underlie greater opioid addiction morbidity in G-allele carriers. Highlights: Oxycodone place preference, locomotor activity, and self-administration were evaluated in male and female Oprm1 A112G mice. 112AA and 112 GG mice showed equivalent conditioned place preference at the doses tested. 112 GG mice showed blunted locomotor responses to oxycodone. 112 GG mice self-administered more oxycodone than 112AA mice. No significant sex differences or sex-by-genotype were observed in any behavioral endpoint.